2022
DOI: 10.3390/jcm11061714
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Adherence to a “GRADIOR” Computer-Based Cognitive Training Program in People with Mild Cognitive Impairment (MCI) and Mild Dementia

Abstract: Background: Computer-based programs have been implemented from a psychosocial approach for the care of people with dementia (PwD). However, several factors may determine adherence of older PwD to this type of treatment. The aim of this paper was to identify the sociodemographic, cognitive, psychological, and physical-health determinants that helped predict adherence or not to a “GRADIOR” computerized cognitive training (CCT) program in people with mild cognitive impairment (MCI) and mild dementia. Method: This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 72 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…Few studies have evaluated its usability and effectiveness in the rehabilitation field. Diaz Baquero et al performed an RCT study on 43 patients with MCI and mild dementia, highlighting good adherence to treatment, good acceptability, and potential efficacy of the device ( 8 ). Another RCT performed by the same authors on 89 people with MCI and dementia demonstrated the benefit of this training on several cognitive domains ( 48 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Few studies have evaluated its usability and effectiveness in the rehabilitation field. Diaz Baquero et al performed an RCT study on 43 patients with MCI and mild dementia, highlighting good adherence to treatment, good acceptability, and potential efficacy of the device ( 8 ). Another RCT performed by the same authors on 89 people with MCI and dementia demonstrated the benefit of this training on several cognitive domains ( 48 ).…”
Section: Resultsmentioning
confidence: 99%
“…For dementia, there is some evidence that computer-based cognitive rehabilitation may be of help in improving different cognitive domains ( 57 ). In particular, the software “GRADIOR” looks promising in the CR field ( 8 , 48–50 ). Moreover, previous studies have applied computerized approaches using photos of the patient and his/her personal surroundings, with positive results ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A study focusing on a computer-based training program more deeply analysed determinants of adherence regarding MCI. They reported lower adherence to the program for participants with MCI, due to executive functioning in attention, working memory or cognitive flexibility [ 38 ]. Taken together, the results, nevertheless, underline the need for higher priority and other consideration of people with MCI to further maintain cognitive ability.…”
Section: Discussionmentioning
confidence: 99%